Medicinal and aromatic species of Asteraceae commercialized in the conurbation Buenos Aires-La Plata (Argentina) - Hurrell, Julio Alberto; Puentes, Jeremías Pedro (Ethnobiology and Conservation, 2013)
The present contribution includes 50 species of Asteraceae whose products are marketed with therapeutic and aromatic purposes in the conurbation Buenos Aires-La Plata, the largest metropolitan area of Argentina. For each species, the scientific and vernacular names, types of products and samples are given. The plant products comprise fresh plants or parts thereof, herbal products, tinctures, and dietary supplements, among others. The uses assigned and the effects scientifically studied are indicated. Also, the ethnobotanical value of the diverse plant products and their commercial circulation are discussed. Circulating products and their uses were studied, both in the restricted context of immigrant segments (Bolivian and Chinese), and in the broader context of general commercial circuit (health food stores, named locally ’dietéticas’). Botanical knowledge of immigrants segments is considered linked to their traditions, and botanical knowledge of general commercial circuit is regarded nontraditional. Research conducted is framed within the urban ethnobotany context. Specially, it addresses some relevant theoretical and methodological topics within discipline: composition of botanical knowledge in urban pluricultural scenarios (linked to traditions, nontraditional), the embodiment of this knowledge in actions (such as selection of products to consume), and the dynamic of changes in urban botanical knowledge (dispersion of products and uses in the commercial circuit and media).